IMPLEMENTASI KEBIJAKAN KARTU JAKARTA PINTAR DI SMP NEGERI 144 JAKARTA - Annisa Aghnia Rahim; Margaretha Suryaningsih (Journal of Public Policy and Management Review, 2016)
Due to high poverty in Jakarta causing students and families cannot get proper education. Economy factor causing education did not prioritized. That excuse force Jakarta Government to build something that support education fund through Jakarta Smart Card. Among all of the Jakarta Smart Cover recipient, in fact there is so much recipient that not appropriate. Another problem is Jakarta Smart Card quota is limited that make so many needy student is hard to occupy their education, especially at 144 Jakarta Junior High School, student still dont get their Jakarta Smart Card. This research proving that Policy Implementation Jakarta Smart Card at 144 Junior High School already going well and effective. There is still some problem such as limited quota that cause student still dont get their Jakarta Smart Card.